2009
DOI: 10.1038/sc.2009.62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seminal citrate level by 1H nuclear magnetic resonance spectroscopy in men with spinal cord injury

Abstract: Patients with SCI have a significant reduction of seminal citrate as a consequence of neurological dysfunction of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The normal value of the citrate concentration in the seminal fluid ([CITRATE]) depends on the methodology used for measurement. A study (19) that evaluated 30 healthy young men (mean age 38.03±10.06 years), using a methodology identical to that of the current study to measure [CITRATE], found a median of [CITRATE] in these men of 44.68mM/l. In the current study, median [CITRATE] was 3.95-fold higher in controls with BPH than in patients with PCa (15.53 vs. 3.93mM/l, p=0.0011).…”
Section: Discussionmentioning
confidence: 61%
“…The normal value of the citrate concentration in the seminal fluid ([CITRATE]) depends on the methodology used for measurement. A study (19) that evaluated 30 healthy young men (mean age 38.03±10.06 years), using a methodology identical to that of the current study to measure [CITRATE], found a median of [CITRATE] in these men of 44.68mM/l. In the current study, median [CITRATE] was 3.95-fold higher in controls with BPH than in patients with PCa (15.53 vs. 3.93mM/l, p=0.0011).…”
Section: Discussionmentioning
confidence: 61%
“…In fact, citrate is the unique prostatic metabolite in seminal plasma investigated by high resolution NMR analysis as a marker to diagnose prostatic cancer [Averna et al 2005] or in men with spinal cord injury [Alexandrino et al 2009]. None of these conditions were detected in our patient population.…”
Section: Resultsmentioning
confidence: 85%
“…The utility of 1 H NMR spectroscopy to highlight changes in the seminal plasma of infertile men with spinal cord injury (SCI) due to neurological dysfunction of the prostate has been demonstrated [3,4]. The presence of higher peptidase activity in infertile men with SCI and that uridine is likely to be an essential precursor to metabolites required for capacitation and is a potential marker for the prognosis of functional fertility recovery in patients with SCI has now been established [24,23].…”
Section: Discussionmentioning
confidence: 99%